IMPLEMENTASI KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENGEMBANGKAN KETERAMPILAN ABAD 21 DI SEKOLAH MENENGAH PERTAMA AL-FALAH DELTASARI SIDOARJO - Zakiyatul Nisa'; Alfiatus Sholiha; Irma Soraya; Asep Saepul Hamdani (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
This research starts from an educational phenomenon that wants to develop learning skills by providing Pancasila lessons and the desire to know the planning, process, and evaluation of project activities to strengthen the profile of Pancasila students in developing 21st-century skills such as creative, critical, communication and collaboration. This research is qualitative research with a descriptive character. The data collection techniques used were in-depth interviews, observation, and documentation. The sampling technique used was nonprobability sampling with the techniques taken, namely purposive sampling and snowball sampling. Data analysis was carried out through data reduction, data presentation and then drawing conclusions. The key informant in this research was the PAI teacher, while other supporting data was obtained through additional informants, namely, the head of the curriculum, driving teachers, and students. The results of this research show that 21st-century learning is a bridge through learning projects to strengthen the profile of Pancasila students. In the concept of the Pancasila student profile, there is learning needed in the 21st Century learning era which is usually called 4C Creativity, Critical thinking, Communication, Collaboration. By learning the Pancasila student profile project, students will gain insight into new skills for the world they will face in the future. The implication of this research is that teachers, especially teachers who teach Pancasila subjects or other terms, can further instill a sense of love for the country and Pancasila, which then has an effect on developing students' talents and skills in carrying out learning at school.